Technology's varying impact on the success of strategic business units within the miles and snow typology - Dvir, Dov; Segev, Eli; Shenhar, Aaron (Strategic Management Journal, 1993)
The high‐tech industry is usually treated as an homogeneous entity, without differentiating between organizations according to the relative importance of technology in their business strategy. This paper investigates the varying impact of technology on the success of strategic business units within the Miles and Snow typology. Although common wisdom might lead to the conclusion that prospectors are more dependent on technological progress than the other strategic types, the results show rather that the influence is greater and more fruitful for the defenders both in the short and the long term.